ARTICULATING GENDER AND HEALTH: PROFESSIONAL QUALIFICATION WITHIN THE SCOPE OF REDE CEGONHA - Enilce de Oliveira Fonseca Sally; Maria Martha de Luna Freire; Helen Campos Ferreira; Sônia Maria Dantas Berger; Marlene Merino Alvarez; Claudia Regina Santos Ribeiro (Universidade do Estado do Rio de Janeiro, 2017)
Educational demands from Rede Cegonha health teams at Metropolitan Region II of Rio de Janeiro inspired a University Extension Project with the goal of contributing to health care improvement. We present a critical and reflective description of this initiative, underscore its processuality and point out its challenges, limits, and potentialities. The approach to gender as a cross-sectional theme, the shared production of knowledge in the educational process pedagogical and the work in a health network have been particularly addressed in the pedagogical policy underlying this study. Based on participatory methodologies, five meetings were held, approaching the following themes in a theoretical and practical perspective: gender and sexuality; violence; feeding and nutrition; health care during pregnancy, at childbirth and until children are two years old. There were varied degrees of gender crossings in the personal and professional lives of the participants, most of whom were women: for example, from restrictions to their choice of education or career opportunities to the current situation in which women are the sole or primary breadwinners but experience inequalities in gendered division of labor. In health services provided to pregnant women, their partners and children, one could still see potentially discriminatory practices; inexperience/embarrassment when dealing with new marital arrangements; feeding myths; reluctance to allow the father's presence and participation. Women's autonomy and right to choice and information were recurrently neglected - from the moment of forced fasting when she is admitted to hospital until the moment a cesarean section is induced. Therefore, it was concluded that it is crucial to include the theme of gender in health professional education and training programs, either at a specific point in time or throughout the whole program. DOI: 10.12957/demetra.2017.28661